PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN IPS MATERI KEHIDUPAN MASYARAKAT INDONESIA PADA MASA PRAAKSARA DAN HINDU TERHADAP HASIL BELAJAR SISWA KELAS VII SMP NEGERI 4 KOTA BOGOR - Ranta Sarjadipura (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
THE APPLICATION OF JIGSAW-TYPE COOPERATIVE LEARNING IN THE SUBJECTS OF INDONESIAN COMMUNITY LIFE DURING THE PRAAKSARA AND HINDU PERIODS ON STUDENT LEARNING OUTCOMES IN CLASS VII JUNIOR HIGH SCHOOL (SMP N 4 KOTA BOGOR)This study aims to measure the learning outcomes of students in the life material of Indonesian society during the pre-literal and Hindu Buddhist periods in class 7E at junior high school (SMP Negeri 4 Bogor) in the 2017-2018 academic year. Another objective is to find out the process of improving student learning outcomes in the life material of Indonesian society during the pre-literacy and Hindu Buddhist periods. Also to find out the magnitude of the increase in student learning outcomes in the life material of Indonesian society during the pre-literacy and Hindu Buddhist periods in class 7 at junior high school This research is a Classroom Action Research by providing action on research subjects in two learning cycles. The results of this study indicate that the application of the jigsaw method to the material of Indonesian society during the pre-literal and Hindu Buddhist periods in class 7E at SMP Negeri 4 Bogor City before applying the learning method has an average value of 62.08. When learning was changed to apply the jigsaw method, the average student learning outcomes increased to 73.75 in cycle I and 80.83 in cycle II. Thus it is concluded that the application of the jigsaw method used by teachers can improve student learning outcomes, therefore researchers suggest that the application of learning methods needs to be socialized and used in social science learning in schools within the Bogor City Education Office.